HARDWARE-SOFTWARE COMPLEX FOR NAVIGATION SATELLITE SYSTEMS AVAILABILITY PREDICTION - Sushych, Oleksii; Prykhodko, Iryna (Proceedings of National Aviation University (archive), 2014)
Development of a hardware-software complex for calculation navigation systems availability in order to improve flight safety aircraft which use satellite navigation.